ID188 A Experiência de Avaliação de Tecnologia em Saúde no Sistema de Saúde Suplementar Brasileiro - Marcus Carvalho Borin; Lélia Maria de Almeida Carvalho; Carina Rejane Martins; Daniel Pitchon dos Reis; Geraldo Jose Coelho Ribeiro; Karina de Castro Zocrato; Marcela Pinto de Freitas; Maria da Glória Cruvinel Horta; Mariana Michel Barbosa; Mariza Cristina Torres Talim; Silvana Marcia Bruschi Kelles (Jornal de Assistência Farmacêutica e Farmacoeconomia)
Introdução